Endovascular treatment strategy and clinical outcome of tentorial dural arteriovenous fistula - Zhang, Guangjian; Zhang, Weiwei; Chang, Hanxiao; Shen, Yuqi; Ma, Chencheng; Mao, Lei; Li, Zheng; Lu, Hua (Frontiers in Neurology, 2024)
Introduction: T o evaluate treatment strategies and clinical outcomes following endovascular embolization of tentorial dural arteriovenous fistulaeTo explore endovascular treatment strategies and clinical outcomes for tentorial dural arteriovenous fistulae. Methods: We retrospectively analyzed 19 patients with tentorial dural arteriovenous fistulae admitted to the Department of Neurosurgery at Jiangsu Provincial People's Hospital between October 2015 to May 2022, all treated with endovascular therapy. To collect and analyze patients' clinical presentation, imaging data, postoperative complications, and prognosis and to analyze the safety and clinical outcomes of endovascular treatment of tentorial dural arteriovenous fistulae. Results: Imaging cure was achieved in 18 patients, with the arterial route chosen for embolization in 17 patients and the venous route in one patient; one patient received partial embolization. Staged embolization was performed in four patients. At postoperative follow-up of 9-83 months (37.8±21.2), all 19 patients recovered well (mMRS score ≤2). Three patients experienced perioperative complications: intraoperative Onyx reflux into the middle cerebral artery in one patient; postoperative permanent limited left visual field loss and deafness in the left ear in one patient; and transient diplopia, vertigo, and decreased pain and temperature sensation of the left limb in one patient, with no abnormalities on post-procedure magnetic reswhich were not abnormal on two magnetic resonance examinations. Seventeen patients completed a postoperative digital subtraction angiography review during follow-up, and one patient had a recurrence of an arteriovenous fistula. Conclusion：Endovascular treatment of tentorial dural arteriovenous fistulas is safe and effective. Reduction of the Borden or Cognard classification via eliminating cortical venous reflux through multi-staged embolization or combined open surgery is a reasonable goal of treatment where complete obliteration of the fistula is not achievable.If the procedure does not result in complete embolization, the Borden or Cognard classification should be lowered, and cortical venous drainage must be